Exposure to secondhand smoke and voluntary adoption of smoke-free home and car rules among non-smoking South African adults - Ayo-Yusuf, Olalekan A (BioMed Central, 2014)
BACKGROUND: Secondhand smoke (SHS) exposure is a well-established health hazard. To determine the effectiveness of existing smoke-free policies and adoption of smoke-free rules in South Africa, we assessed exposure to SHS from several sources among non-smoking adults during 2010. METHODS: Data were analyzed for 3,094 adults aged ≥16 years who participated in the 2010 South African Social Attitudes Survey. Descriptive statistics and multivariate analyses were used to assess presence of smoke-free rules among all South Africans, and prevalence and correlates of SHS exposure at work, at home, and at hospitality venues among non-smokers. RESULTS: Overall, 70.6% of all South African adults had 100% smoke-free rules in their private cars, 62.5% in their homes, while 63.9% worked in places with 100% smoke-free policies. Overall, 55.9% of all non-smokers reported exposure to SHS from at least one source (i.e., in the home, workplace or at a hospitality venue). By specific source of exposure, 18.4% reported being exposed to SHS at work, 25.2% at home, 33.4% in a restaurant, and 32.7% at a bar. Presence of work bans on indoor smoking conferred lower likelihood of SHS exposure at work among non-smokers (adjusted odds ratio [aOR] = 0.23; 95% CI: 0.09-0.60). Similarly, smoke-free home rules decreased the odds of being exposed to SHS at home among non-smokers (aOR =0.16; 95% CI: 0.09-0.30). CONCLUSION: Over half of South African adults reported SHS exposure in the home or at public places such as the workplace and at hospitality venues. This underscores the need for comprehensive smoke-free laws that prohibit smoking in all public indoor areas without exemptions.